2003
DOI: 10.1161/01.cir.0000080504.70265.05
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anterior Mitral Leaflet Second-Order Chordae Tendineae on Left Ventricular Systolic Function

Abstract: Background-The contribution of anterior mitral leaflet second-order ("strut") chordae tendineae to left ventricular (LV) systolic mechanics is debated; we measured the in vivo contribution of anterior chordae tendineae (ACT) and posterior chordae tendineae (PCT) to regional and global LV contractile function. Methods and Results-Eight sheep had radiopaque markers implanted in the LV epicardium, partitioning the ventricle into 12 regions. Microminiature force transducers and snares were sutured to anterior le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 26 publications
(20 reference statements)
1
39
0
1
Order By: Relevance
“…Although we believe that the second-order chordae are important for valvular-ventricular interaction, debate exists because reports from a previous experiment in this laboratory failed to demonstrate changes in either load-dependent or load-independent indices of global LV function after transection of second-order chordae, 12,13 and Messas et al observed no change in LV ejection fraction after chordal cutting. 10,11 Alterations in regional LV systolic dysfunction (decreased fractional area shortening and decreased regional preload recruitable stroke work) adjacent to the PM insertion sites, however, have been observed.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…Although we believe that the second-order chordae are important for valvular-ventricular interaction, debate exists because reports from a previous experiment in this laboratory failed to demonstrate changes in either load-dependent or load-independent indices of global LV function after transection of second-order chordae, 12,13 and Messas et al observed no change in LV ejection fraction after chordal cutting. 10,11 Alterations in regional LV systolic dysfunction (decreased fractional area shortening and decreased regional preload recruitable stroke work) adjacent to the PM insertion sites, however, have been observed.…”
mentioning
confidence: 73%
“…In local cardiac coordinates [X 1 , X 2 , X 3 ], the 3 normal strain components measure myocardial stretch or shortening along the circumferential (E 11 ), longitudinal (E 22 ), and radial (E 33 ) cardiac axes. The 3 shear strains (E 12 , E 13 , and E 23 ) represent angle changes between pairs of originally orthogonal coordinate axes. Strains were interpolated along the centroid of the bead columns at 1% increments of wall depth from the epicardium at ED.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MCT link the free edges and the ventricular surface of both leaflets of the MV to the papillary muscles, thus preventing the backflow of the blood into the left atrium during ventricular contraction. Several equivalent classifications for the MCT are proposed in the literature [13,29,12,26,27,3,20,31,24]. In general, the MCTs are classified according to their insertion sites on the mitral leaflets.…”
Section: The Mitral Valve and The Mitral Chordae Tendineaementioning
confidence: 99%